(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article focuses on problems connected with handling expenses beard by the investor. The paper also characterizes the factors which influence the height of distribu-tion expenses and presents their impact on returning rate from investment in the Open Investment Founds